Factors That Predict the Success of Laparoscopic Common Bile Duct Exploration for Choledocholithiasis: A 10-Year Study. Issue 5 (October 2021) - Kao, Chien-Tse; Seagar, Rosemary; Heathcock, Daniel; Tacey, Mark; Lai, Jiun Miin; Yong, Tuck; Houli, Nezor; Bird, David; Hodgson, Russell
Abstract : Background: Laparoscopic common bile duct exploration (LCBDE) can be performed to treat choledocholithiasis at the time of laparoscopic cholecystectomy. The aim of this study was to identify factors that predict the success of LCBDE. Materials and Methods: A retrospective audit was performed on patients who underwent LCBDE for the management of choledocholithiasis at Northern Health between 2008 and 2018. Results: A total of 513 patients were identified with an overall success rate of 90.8%. Most LCBDE were done through a transcystic approach with the remainder through a choledochotomy. When comparing patients with a successful operation to those that were unsuccessful, univariate analysis demonstrated significant differences in preoperative white cell count and number of duct stones found. Age and elevated nonbilirubin liver function tests were found to be significant factors associated with the failure of LCBDE on multivariate analysis. The likelihood of a failed operation in those with multiple stones was observed to be almost halved compared with patients with single stone although this did not reach significance [odds ratio (OR): 0.53, 95% confidence interval (CI): 0.28-1.01, P =0.055]. Multivariate analysis indicated that unsuccessful procedures (OR: 10.13, 95% CI: 4.34-23.65, P <0.001) and multiple duct stones (OR: 3.79, 95% CI: 1.66-8.67, P =0.002) were associated with an increased risk of severe complications. Conclusions: A single impacted stone may be more difficult to remove, however complications were more likely to be associated with multiple duct stones. With no other clinically relevant predictive factors, and because of the high success of the procedure and the low morbidity, LCBDE remains an option for all patients with choledocholithiasis.